REVIEWING THE EXISTENCE OF COOPERATION BETWEEN THE DIRECTORATE GENERAL OF IMMIGRATION AND SPONSORS OF INDONESIAN MIGRANT WORKERS - Janurdi Tirto Utomo; Javier Saviola; Kevin Abel Panjaitan (Jurnal Ilmiah Advokasi, 2023)
Based on data owned by the Ministry of State-Owned Enterprises (BUMN), donations in the form of state foreign exchange from Indonesian Migrant Workers (PMI) reached IDR 130 trillion in 2021.  The benefits provided by the existence of Indonesian migrant workers are certainly beneficial for the Indonesian state itself. Because it is one of the great hopes to help provide foreign exchange for the country, of course it needs to be considered by our government. The empowerment and utilization of Indonesian migrant workers needs to be done very wisely. It is worth considering many things, what's more, Indonesian migrant workers are a very important and sensitive element given that they are human beings.  In this case, the existence of Indonesian Migrant Workers is needed by someone as a liaison between the PMI and matters related to administration or so on. The person or company responsible for this matter is commonly referred to as a sponsor or guarantor. The existence of sponsors or guarantors is also needed to bridge the relationship between Indonesian Migrant Workers, which in this case is the Directorate General of Immigration This research aims to review the existence of cooperation between immigration offices and sponsors of Indonesian migrant workers.  The method used in this study is the Normative-Empirical method which is carried out by elaborating the  written hukum element  which is then supported by the addition of data or empirical elements.Keywords : Indonesian Migrant Workers, Sponsors, Directorate General of Immigration.